2022
DOI: 10.3390/ijms23116294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia-Induced Micro-RNAs Expression on Oncogenesis

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression at the post-transcriptional level. An aberrant regulation of gene expression by miRNAs is associated with numerous diseases, including cancer. MiRNAs expression can be influenced by various stimuli, among which hypoxia; however, the effects of different types of continuous hypoxia (moderate or marked) on miRNAs are still poorly studied. Lately, some hypoxia-inducible miRNAs (HRMs, hypoxia-regulated miRNAs) have been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Other forms of ncRNAs include long non-coding RNAs (lncRNA), PIWI-interacting RNAs (piRNA), small interfering RNAs (siRNA), and microRNAs (miRNA) [ 137 , 138 ]. It is well known that the hypoxic microenvironment in MPM interferes with a range of miRNAs and that some miRNAs target HIF1α [ 139 , 140 , 141 , 142 ]. With respect to MPM, published data point out that let-7c-5p and miR-151-5p can be considered “hypoxamiRs” involved in tumor initiation and EMT maintenance, altered metabolism, chemoresistance, and poor prognosis [ 78 ].…”
Section: Trancriptome and Secretome Profile Of Mpmmentioning
confidence: 99%
“…Other forms of ncRNAs include long non-coding RNAs (lncRNA), PIWI-interacting RNAs (piRNA), small interfering RNAs (siRNA), and microRNAs (miRNA) [ 137 , 138 ]. It is well known that the hypoxic microenvironment in MPM interferes with a range of miRNAs and that some miRNAs target HIF1α [ 139 , 140 , 141 , 142 ]. With respect to MPM, published data point out that let-7c-5p and miR-151-5p can be considered “hypoxamiRs” involved in tumor initiation and EMT maintenance, altered metabolism, chemoresistance, and poor prognosis [ 78 ].…”
Section: Trancriptome and Secretome Profile Of Mpmmentioning
confidence: 99%
“…NH appears to involve a hypoxia-inducible factor (HIF), a regulator of oxygen metabolism, with activation of various pathophysiological pathways that cause the risk of developing chronic diseases such as diabetes, insulin resistance or cardiovascular diseases [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the alterations of gas exchanges during sleep cause an increased risk of a large number of diseases [ 5 ]. Several studies have demonstrated a directly proportional relationship between the number of cardiovascular risk factors, such as the development of arrhythmias, and OSA severity [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%